A Loving Kind of Knowing: Connatural Knowledge as a Means of Knowing God in Thomas Aquinas’s Summa Theologica - Duke, Meghan (Lumen et Vita, 2018)
In his exegesis of Romans 8:15-16, Thomas Aquinas asks how it is that the Holy Spirit bears testimony in us that we are the children of God. He responds that the Spirit bears testimony “through the effect of filial love he produces in us. ” At least in some circumstances, Aquinas suggests, we can come to know God through our experience of loving him. But Aquinas, following a long tradition, teaches that we love things insofar as we know them as good (cf: I-II, q.9, a.1, corpus and ad.3). How then can love give rise to knowledge? Aquinas’s teaching in the Summa Theologica on the Holy Spirit’s gift of wisdom provides a key to this question. The gift of wisdom makes use of the love of charity to know God (II-II, q.45). Charity, by making us “connatural” with God, can give rise to knowledge of God. I will then consider how the Holy Spirit’s gift of wisdom relates to the science of theology. The gift of wisdom, however, does not offer an independent or parallel path to knowledge of God, but rather, depends on faith and is the perfection to which the science of sacred is oriented.